Fenomena Pernikahan Dini Di Desa Loloan Kecamatan Bayan Kabupaten Lombok Utara - M Junaidi; Nidya Putri Syahida; Nur aini (JIAP (Jurnal Ilmu Administrasi Publik), 2019)
North Lombok Regency in 2016 recorded the age of early marriage reached 2,026 incidents in 5 sub-districts including Bayan Subdistrict, which pocketed the highest number of incidents of early marriage of 1,021 children. This also happened in the Loloan Village, Bayan District, North Lombok Regency The objectives of this study are (1) to find out the barriers to the role of the village government in dealing with the rampant phenomenon of early marriage in Loloan Village, Bayan District, North Lombok Regency (2) to find out the village government's efforts to deal with the rampant phenomenon of early marriage in Loloan Village, Bayan District, North Lombok Regency ( 3) To find out the supporting and inhibiting factors in suppressing the phenomenon of early marriage in Loloan Village, Bayan District, North Lombok Regency. This study uses a type of qualitative-descriptive research. Sources of data in this study are: Informants or resource persons, namely village heads, community leaders, young women in the village, early marriages themselves. Data collection techniques used in this study are: observation, interviews, documentation. The data analysis technique used in this study is data reduction, data presentation and conclusion drawing. Based on the results of the study that early marriage in Loloan Village has increased every year. Even though the Village Government has implemented Village Regulations in implementing the Village government program, however, there are various obstacles in suppressing the phenomenon of early marriage including economic factors, socio-cultural factors and social factors.